1988
DOI: 10.1093/njaf/5.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Using Regression Equations for Estimating Tree Biomass

Abstract: Tree biomass is most commonly estimated using regressions of green or dry weight to tree dimensions. Rarely is it feasible for managers to develop their own predictive equations, so they must rely on published regressions and weight tables developed from those regressions. A guide is presented that will help each manager select the most appropriate equation available for a given situation. We also provide common regression models currently in use, statistics for comparing published equations, and practical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The underestimation is consistent with the previous studies of biomass equations that generalized 26 urban-based species-specific allometric equations [49]. Part of the underestimation was probably caused by the inherent bias in applying logarithmic transformations when developing these equations [95,96,98,100]. It was found that logarithmic transformations could cause a slight downward bias when equations are converted back to compute biomass in measured units.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The underestimation is consistent with the previous studies of biomass equations that generalized 26 urban-based species-specific allometric equations [49]. Part of the underestimation was probably caused by the inherent bias in applying logarithmic transformations when developing these equations [95,96,98,100]. It was found that logarithmic transformations could cause a slight downward bias when equations are converted back to compute biomass in measured units.…”
Section: Discussionsupporting
confidence: 88%
“…5) are the transformed coefficients from the corresponding regression equations. Four different criteria were computed to cross-validate the performance of Equations (9)-(13) [95,98]: The linear regression through the origin, the paired sample t-test, the root mean square error (RMSE), and the mean relative difference (MRD). The independent data points reserved for validation were first tested for normality with the Shapiro-Wilk test [97].…”
Section: Regression Analysis and Statistical Evaluationmentioning
confidence: 99%
“…For species with several equations available (e.g. Acer saccharum ), preference was given to equations developed in ecologically similar sites (Crow & Schlaegel, 1988), rather than to those from geographically proximate sites. Allometric equations for ‘general hardwoods’≥ 10 cm d.b.h.…”
Section: Methodsmentioning
confidence: 99%
“…where Wis weight per tree of above-ground biomass, D is stem diameter at 1 37 m, and a and b are empirically determined constants (Whittaker & Marks 1975;Parde 1980), although many other equations have been used (Parde 1980;Crow 1988 Hence, E may be viewed as the product of two components: the first related to the size of the plant and the relative allocation of biomass to leaves versus wood (a b c-' Db-I -d) and the second related to instantaneous diameter growth rate (dD/dt). The two components are not uniquely related, in that many combinations are possible depending on stand history and competitive regime.…”
Section: Theory E Versus Lai As An Index To Competitionmentioning
confidence: 99%